Protective effect of Salvia miltiorrhiza and Carthamus tinctorius extract against lipopolysaccharide-induced liver injury - Gao, Li-Na (World J Gastroenterol, 2015)
AIM: To investigate the hepatoprotective effects and mechanisms of an extract of Salvia miltiorrhiza and Carthamus tinctorius in vivo. METHODS: C57BL/6J mice were randomly assigned to five groups and intraperitoneally administered 0.9% saline, Salvia miltiorrhiza and Carthamus tinctorius extract [Danhong injection (DHI), 0.75 and 3 g/kg mixed extract] or reduced glutathione for injection (RGI, 300 mg/kg) for 30 min before exposure to lipopolysaccharide (LPS, 16 mg/kg). After intraperitoneal LPS stimulation for 90 min or 6 h, the mice were sacrificed by ether anaesthesia, and serum and liver samples were collected. Histological analysis (H&E) and terminal deoxynucleotidyl transferase-mediated dUTP nick end-labelling (TUNEL) staining were performed. Alanine transferase (ALT), aspartate transaminase (AST), total bilirubin (TBil), glutathione-S-transferase (GST), malondialdehyde (MDA), tumour necrosis factor (TNF)-α, interleukin (IL)-6, and caspase-3 levels were measured. Bax, Bcl-2, P-IκBα, IκBα, P-NF-κB p65, and NF-κB p65 protein levels were determined by Western blot. TNF-α, IL-6, caspase-3, Bax and Bcl-2 mRNA expression was measured by real-time reverse transcription-polymerase chain reaction (RT-PCR). RESULTS: Hematoxylin-eosin staining and TUNEL results suggested that DHI (3 g/kg) treatment alleviated inflammatory and apoptotic (P < 0.01) injury in the liver of mice. DHI treatment dose-dependently blunted the abnormal changes in biochemical parameters such as ALT (72.53 ± 2.83 for 3 g/kg, P < 0.01), AST (76.97 ± 5.00 for 3 g/kg, P < 0.01), TBil (1.17 ± 0.10 for 3 g/kg, P < 0.01), MDA (0.81 ± 0.36 for 3 g/kg, P < 0.01), and GST (358.86 ± 12.09 for 3 g/kg, P < 0.01). Moreover, DHI (3 g/kg) remarkably decreased LPS-induced protein expression of TNF-α (340.55 ± 10.18 for 3 g/kg, P < 0.01), IL-6 (261.34 ± 10.18 for 3 g/kg, P < 0.01), and enzyme activity of caspase-3 (0.93 ± 0.029 for 3 g/kg, P < 0.01). The LPS-induced mRNA expression of TNF-α, IL-6 and caspase-3 was also decreased by DHI. Western blot analysis revealed that DHI antagonised LPS-stimulated decrease of Bcl-2 and increase of Bax protein expression. Furthermore, DHI inhibited LPS-induced IκBα and NF-κB p65 phosphorylation. CONCLUSION: DHI may be a multi-function protectant against acute hepatic injury in mice through its anti-inflammatory, anti-oxidative and anti-apoptotic activities.